Respostas
respondido por:
6
an = 2 + (50 - 1) x 4
an = 2 + 200 - 4
an = 2 +196
an = 198
Sn = ((2 + 198) x 50)/2
Sn = (200 x 50)/2
Sn = 10000/2
Sn = 5000
an = 2 + 200 - 4
an = 2 +196
an = 198
Sn = ((2 + 198) x 50)/2
Sn = (200 x 50)/2
Sn = 10000/2
Sn = 5000
respondido por:
3
P.A = (2,6,10...)
An = 2 + (50 - 1) x 4
an = 2 + 200 - 4
an = 2 +196
an = 198
Sn = ((2 + 198) x 50)/2
Sn = (200 x 50)/2
Sn = 10000/2
Sn = 5000
Espero ter ajudadoo!!
An = 2 + (50 - 1) x 4
an = 2 + 200 - 4
an = 2 +196
an = 198
Sn = ((2 + 198) x 50)/2
Sn = (200 x 50)/2
Sn = 10000/2
Sn = 5000
Espero ter ajudadoo!!
Perguntas similares
6 anos atrás
8 anos atrás
8 anos atrás
8 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás